Status of liquid profiling in precision oncology: the need for integrative diagnostics for successful implementation into standard care - Froelich, Matthias F.; Schönberg, Stefan; Neumaier, Michael; Haselmann, Verena (Journal of laboratory medicine, 2022)
The liquid profiling approach is currently at the threshold of translation from research application in various clinical trials to introduction into the management of cancer patients in the context of clinical care. Routine application has focused primarily on the analysis of single blood-based biomarkers for companion diagnostics. However, liquid profiling promises much broader diagnostic potential, which is discussed and illustrated in this manuscript through several case reports. These clinical cases range from identification of druggable targets to the detection of subclonal resistance mechanisms. In addition, liquid profiling can be used in clinical practice to identify complex molecular patterns or as a personalized tumor marker for patient-specific monitoring of response to treatment. These examples highlight both the value and limitations of liquid profiling in various clinical settings, which could be overcome by an integrative diagnostic approach with imaging techniques. The complementary advantages of both diagnostics approaches will allow combining high sensitivity with genetic tumor profiling and topologic assignment. Therefore, we advocate interdisciplinary integrated collaboration between laboratory and imaging experts to unravel the potentials of precision diagnostics in cancer care.
Gesehen am 21.12.2022